Much Lower Prevalence and Mortality of Chronic Obstructive Pulmonary Disease in Japan Than in the United States Despite Higher Smoking Rates: A Meta-Analysis/Systematic Review - Akira Sekikawa; Mengyi Li; Niva Joshi; Brandon Herbert; Curtis Tilves; Chendi Cui; Shiyao Gao; Yuefang Chang; Yasutaka Nakano; Frank C Sciurba (Journal of Epidemiology)
Background: A recent systematic review showed Japan’s mortality from chronic obstructive pulmonary disease (COPD) is the lowest among 204 countries, despite notably higher smoking rates in men in Japan than in the United States. This study aims to compare (1) trends in smoking rates, (2) trends in COPD mortality, and (3) the spirometry-based COPD prevalence in the general adult population between Japan and the United States. Methods: Age- and sex-specific smoking rates from the 1980s through 2010s and COPD mortality from 1999 through 2019 were obtained from national surveys and official statistics (International Classification of Diseases-10th codes J40–44), respectively. A systematic review and meta-analysis was performed to estimate COPD prevalence in Japan, while the National Health and Nutrition Examination Survey 2007–2012 was used for the United States. A fixed ratio of 0.7 of forced expiratory volume in the first second of forced vital capacity was used to define COPD. Results: Over the past 4 decades, men in Japan consistently had 20–30% higher smoking rates than their United States counterparts. From 1999–2019, age-adjusted COPD mortality in men in Japan was only a third of the United States, whereas that in women was less than a tenth in 2019. Synthesizing data from 11 studies, involving 89,955 participants, Japan’s COPD prevalence was more than 10% lower than in the United States in almost all age groups for both sexes. Conclusion: This study showed markedly lower rates of COPD in Japan than in the United States. Investigating factors contributing to the paradoxical observations could lead to advancing COPD risk reduction strategies.